COMPLIANCE OF HEALTHCARE STAFF TOWARDS INFECTION CONTROL PRECAUTIONS IN HEMODIALYSIS UNITS – GAZA GOVERNORATES - Tabash, Mohammed; Kashkash, Raid; Eljedi, Ashraf (Innovare Journal Health Sciences, 2018)
Abstract: Objective: Health care associated infections are the most frequent adverse event in health care delivery, which lead to significant mortality and financial burden for health systems. This study aimed to assess the health care providers' compliance with infection control practices in the hemodialysis units. Methods: A cross sectional, analytical design with census sample was used. The data were collected using interviewing questionnaire and observational checklist for the practice of health care providers. In total, 77 questionnaires were collected, 228 practice observational checklists and five physical environment observational checklists. Results: The study findings revealed that hospital management does not practice its role efficiently in encouraging health care providers to be compliant with infection prevention and control protocol. Findings of the study revealed that the majority of the study participants had not adequate training (79.2%) about the infection prevention and control protocol. The findings of the standard precaution showed that the compliance with hand hygiene score was 56.2%; personnel protective equipment score was 87.5%; using waste management score was 39.6%; environmental infection control practices score was 54.3% and aseptic technique score was 62.8%. however, additional precaution score was 56.5%. Moreover, the study revealed that 45.8% of the health care providers were exposed to an injury from used needles or sharp medical instruments. The study also found that 93.5% of the health care providers working in the hemodialysis unit received the recommended three doses of hepatitis B vaccine. Finally, the study showed that there are a statistical deference's between hospitals and all standard precaution domains (P value= .000), while part of standard precaution domains (personnel protective equipment, waste management, environmental infection control practices) had a statistical difference with occupational type respectively (.000, .008, .031). Conclusion: There is a need to develop a Palestinian infection prevention and control protocol special for hemodialysis unit. A continuous education and training programs for healthcare staff and physical environmental fitness concerning Infection Prevention and Control protocol should be implemented. Key words: Hospital acquired, Hemodialysis units, Infection control, Compliance